Peran BUMDes dalam Pengelolaan Alih Fungsi Lahan Desa Menjadi Wisata Edukasi - Virdaus, Ruly; Sugiyanto, Sugiyanto; Asmara, Rosihan (Universitas Musamus, Merauke, Papua, 2024)
In general, BUMDes is a form of collective village economic enterprise and is a learning opportunity for village residents. The aim of this research is to describe the role of BUMDes in managing the conversion of village land for educational tourism, precisely in Pejambon village, Sumberrejo subdistrict, describe the performance of BUMDes in improving the village economy through managing the conversion of village land for educational tourism, precisely in Pejambon village, Sumberrejo subdistrict. The method used in this research is descriptive qualitative which uses combined (quantitative) data by organizing the data obtained into categories, analyzing important data, and compiling the appropriate data in the form of a report and drawing conclusions so that it is easy to understand. The method used in data analysis, namely qualitative data, includes data reduction, data display, conclusions and verification. Meanwhile, quantitative data analysis includes determining the number of classes, range and division of intervals within classes. From the results of the research above, it can be concluded that infrastructure development in managing the conversion of village land into Pejambon Educational Tourism has experienced the most significant decline. Management and marketing/promotion are considered to be quite good. Meanwhile, providing training and human resource development as well as financial management are still tasks that must be completed by BUMDes. However, most people feel that the conversion of village land into Pejambon Educational Tourism has increased income and improved community welfare so that the results can be used to meet daily needs.